Unemployment and Women Education - Thingbaijam, Sharmila; Thaimei, Thaithuilu (JOURNAL OF INDIAN EDUCATION, 2021)
Education is a very important tool for human resource development particularly women education. The significance of the study is to highlight the unemployment rate among women, there causes and effect in the day-to-day life of the people of Ragailong. In the present study an attempt is made to explain the literacy and unemployment rate of the women of Ragailong. It also highlighted that most of the married women though educated and qualified are deprived from working and finding a job because of their responsibility to the family. From the study, it was found that educationally and socially, the present condition and status of the people of Ragailong village has improved and developed a lot in comparison to the past, as the literacy and employment rates are found to be high in the village but it is definitely high time for all the people to give self-employment a prominent place in the society rather than waiting for the government job offers. Also, both women and men should be given equal rights and freedom to freely choose the job they wish to pursue to aid in women development and empowerment